Simple method for screening aflatoxin-producing molds by UV photography. - Yabe, K (1987)
UV absorption by aflatoxins was monitored in GY agar medium by UV photography. In the UV photographs, aflatoxin-producing molds were identified as gray or black colonies, whereas aflatoxin-nonproducing molds appeared as white colonies. By cellophane transplantation experiments and silica gel thin-layer chromatography, the products absorbing UV light substantially were found to be mainly aflatoxins B1 and G1 excreted from the mold mycelium into the agar medium. UV absorption did not occur when the agar medium contained aflatoxin-noninducible carbon sources instead of glucose. Various inhibitors of aflatoxin production, such as dichlorovos and dimethyl sulfoxide, also decreased the intensity of UV absorption. These results indicate that this technique can be used as a simple, safe, and rapid method of screening aflatoxin-producing molds.